Emerging Treatment Of Rheumatoid Arthritis - Use of Biologic Agents - Rahman, Md Monzur (KYAMC Journal, 2013)
Until now there no curative treatment for Rheumatoid arthritis. As the pathogenesis of the disease is now greatly unveiled, and role of many immunologic key-molecules have been understood, new agents called 'biologic agents' are discovered, which are being used as therapeutic agents to target the key-molecules with great success. Remarkable results have been achieved ( even cure in significant number of cases, when treatment started early) when some of these agents are used in combination with Methotrexate. Notable among these agents are anti-TNF agents, IL-1 and IL-6 inhibitors, B-cell antagonists (e.g. Rituximab), T-cell blocking agents, RANKL inhibitors ( denosumab) etc. The main obstacle to their use is treir high cost, for which reason they out of reach of general people. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13518 KYAMC Journal Vol.2(1) 2011 pp.132-139